Using Laactract's Theory to Find Out Millennia Generations Friendship Problems (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
The phenomenon of juvenile delinquency and its relation to deviant behavior makes education enthusiasts and practitioners continue to seek alternative solutions for this problem. This case is most important thing, because the phenomenon of dissemination is very worrying especially in the modernization era which marked by the rapid development of information technology and western culture into the private territory, until the millennia generation to form certain groups or gangs in accordance with the comfort of children, the formation of this group does not always have a positive impact on a person's development, but the vast majority of these particular groups have a negative impact on a person. This paper explores the issue to find alternative solutions for the problem. The paradigm of revelation used in this paper is QS. QS.49: 13. This study offers the idea of Law of acttractions theory which means that man as a social being can not necessarily break away from the social facts in which he is located and with whom he is socially dealing, what is necessary is to regulate the emotions and thoughts in order to always be positive for everything. Emotional and attitude arrangement can be done with constructive education process through heterogeneous communication, in this case man trying to realize, achieve and realize what is desired (dream) with positive thinking, will be achieved (get)